Continuous biodiesel process using ultrasonic in-line reactor for Jatropha Curcas Oil (JCO) - Mohd Yusoff, Nurrul Rahmah (2017)
Biodiesel is an alternative fuel for replacing diesel fuel in compression ignition engines. Due to the complexity of the diesel fuel production and exhaust emissions from petroleum-fuelled engines will give negative impact to the environment. In this study, the sodium hydroxide as the catalyst was used to react with methanol for obtaining chemical compound that is called methyl ester which is known as biodiesel. The method used are Ultrasonic. Basically, this method will reduce the reaction time on the conversation of jatropha curcas oil (JCO) into biodiesel. The experiment was to determine the effect of esters contents by reaction time, molar ratio methanol (MeOH) to JCO, the amount of catalyst, frequency and power output of ultrasonic using ultrasonic in-line reactor. The optimum production of biodiesel was achieved at 7 minutes of reaction time, 1%wt of catalyst concentration and molar ratio methanol to oil 12:1, frequency ultrasonic of 20 KHz and ultrasonic output 600 Watt at temperature 65°C. The biodiesel produced by this method has been referred according to ASTM D6751. From the result, the biodiesel produced from this method has satisfied the requirement biodiesel standard. This optimum result in this research can be used to run larger pilot plant designed for industry.